Training medical students in physical examination and point-of-care ultrasound: An assessment of the needs and barriers to acquiring skills in point-of-care ultrasound - Rajkumar Rajendram; Abdullah O Alrasheed; Abdulaziz A Boqaeid; Faris K Alkharashi; Salman S Qasim; Arif Hussain (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: With growth of the use of point of care ultrasound (PoCUS) around the world, some medical schools have incorporated this skill into their undergraduate curricula. However, because of epidemiology of disease and regional differences in approaches to patient care, global application of PoCUS might not be possible. Before creating a PoCUS teaching course, it is critical to perform a needs analysis and recognize the training obstacles. MATERIALS AND METHODS: A validated online questionnaire was given to final-year medical students at our institution to evaluate their perceptions of the applicability of specific clinical findings, and their own capability to detect these signs clinically and with PoCUS. The skill insufficiency was assessed by deducting the self-reported clinical and ultrasound skill level from the perceived usefulness of each clinical finding. RESULTS: The levels of expertise and knowledge in the 229 students who participated were not up to the expected standard. The applicability of detection of abdominal aortic aneurysm (AAA) (3.9 ± standard deviation [SD] 1.4) was the highest. However, detection of interstitial syndrome (3.0 ± SD 1.1) was perceived as the least applicable. The deficit was highest in the detection of AAA (mean 0.95 ± SD 2.4) and lowest for hepatomegaly (mean 0.57 ± SD 2.3). Although the majority agreed that training of preclinical and clinical medical students would be beneficial, 52 (22.7%) showed no interest, and 60% (n = 136) reported that they did not have the time to develop the skill. CONCLUSION: Although medical students in Saudi Arabia claim that PoCUS is an important skill, there are significant gaps in their skill, indicating the need for PoCUS training. However, a number of obstacles must be overcome in the process.